In-hospital outcomes of patients with chronic kidney disease undergoing percutaneous coronary intervention for chronic total occlusion: a systematic review and meta-analysis. Issue 8 (December 2021) - Farrukh Mustafa, Syed; Zafar, Meer R.; Vira, Amit; Halalau, Alexandra; Rabah, Maher; Dixon, Simon; Hanson, Ivan
Abstract : Background: The relative safety and efficacy of percutaneous coronary intervention (PCI) for chronic total occlusions (CTO) in patients with chronic kidney disease (CKD) have not been well defined. We performed a systematic review and meta-analysis of observational studies to assess in-hospital outcomes in this population. Methods: We searched MEDLINE, EMBASE, and Cochrane Library databases from inception to April 2020 for all clinical trials and observational studies. Five observational studies with a total of 6769 patients met our inclusion criteria. Patients were divided into two groups based on estimated glomerular filtration rate (eGFR <60 ml/min/1.73m 2 in CKD group and ≥ 60 ml/min/1.73m 2 in non-CKD group). The primary outcome was in-hospital mortality. Secondary outcomes were acute kidney injury, coronary injury (perforation, dissection or tamponade), stroke and procedural success. Mantel–Haenszel random-effects model was used to calculate the odds ratio (OR) and 95% confidence intervals (CI). Results: In-hospital mortality was significantly higher among patients with CKD undergoing PCI for CTO (OR: 5.16, 95% CI: 2.60–10.26, P < 0.00001). Acute kidney injury (OR: 2.54, 95% CI: 1.89–3.40, P < 0.00001) and major bleeding (OR: 2.58, 95% CI: 1.20–5.54, P < 0.01) were also more common in the CKD group. No significant difference was observed in the occurrence of stroke (OR: 2.36, 95% CI: 0.74–7.54, P < 0.15) or coronary injury (OR: 1.38, 95% CI: 0.98–1.93, P < 0.06) between the two groups. Non-CKD patients had a higher likelihood of procedural success compared to CKD patients (OR: 0.66, 95% CI: 0.57–0.77, P < 0.00001). Conclusion: Patients with CKD undergoing PCI for CTO have a significantly higher risk of in-hospital mortality, acute kidney injury and major bleeding when compared to non-CKD patients. They also have a lower procedural success rate.